STUDENTS’ NEEDS ANALYSIS IN DEVELOPING ENGLISH FOR TOURISM LEARNING MATERIALS AT SMA ASTIKA DHARMA - Ni Luh Sri Meilani; Pande Agus Adiwijaya; Md Andhi Supriatna Arna (Universitas Pendidikan Ganesha, 2022)
This study aimed at determining the needs of students in the development of English for tourism learning materials at SMA Astika Dharma. This study used a descriptive method with reference to a qualitative approach. The research subjects of this field study were students of class X and XI of SMA Astika Dharma. The data collection technique used was a questionnaire technique to determine the needs of students in developing tourism learning materials. The instrument of data collection in this study was a questionnaire. This study uses descriptive statistical analysis techniques used to process questionnaire data on student needs in the development of tourism teaching materials at SMK Astika Dharma. The results showed that (1) English for Tourism is different from general English, (2) The digital teaching materials needed by students are digital teaching materials that are easily accessible, easy to understand, visually appealing, have audio access, and can be accessed anytime, (3) The language used for digital teaching materials for tourism English lessons is Indonesian and English (bilingual), (4) The form of digital tourism teaching materials desired by the majority of students is in the form of learning videos.